UV-Vis Spectrophotometric Determination of Aluminum in Feminine Antiperspirants: Method Development and Validation - Mateo Saavedra, Antony Javier; Buitron Mercado, Melissa Francesca; Gonzales-Condori, Elvis; Carpio Carpio, José Miguel; Villanueva-Salas, Jose Antonio; Medina Pérez, Jeaneth Marisol; Choquenaira-Quispe, Celia (LACCEI, 2025)
Aluminum is the third most abundant metal on earth and is currently widely used in industrial, technological and medical sectors, including pharmaceuticals and personal care products. However, in recent years, several studies suggest possible health risks of aluminum, being associated with neurotoxicity, Alzheimer's disease and breast cancer. Therefore, the aim of this study was to propose, develop and validate a simple, reliable and accessible UV-VIS spectrophotometric method for the quantification of aluminum by means of the aluminum-alizarin complex. The method proved to be linear with a coefficient of determination R2 of 0.9998, precise with a relative standard deviation (RSD) of less than 11% and accurate with recovery percentages higher than 80% and lower than 110%, as stipulated by the AOAC. In conclusion, the method proved to be simple, accessible, reliable, precise and accurate for the quantification of aluminum in antiperspirant samples.